Swedish Legislation Regarding Forensic DNA Elimination Databases. Issue 1 (7th June 2016) - Ansell, Ricky; Widén, Christina
ABSTRACT: Evidence contaminated with DNA from staff, police, and other individuals can have a dramatic impact on an investigation and can mislead police inquiries. Forensic DNA elimination databases (EDB) are used to minimize the risks associated with DNA contamination. Central issues with maintaining such databases include the basis for sample collection, sample, and profile integrity, as well as retention times, database access, and procedures when a database match occurs. Following years of discussion, debate, and the use of an "in house" EDB at the Swedish National Forensic Centre (NFC), these issues have now been resolved by passing legislation on DNA EDB. According to the legislation, sampling for EDB purposes is mandatory for certain forensic professionals, as well as for other individuals who need access to the premises handling DNA evidence. In the event of a database match, the match can only be reviewed and evaluated for quality purposes and the name of the donor cannot be disclosed to the crime inquiry. Thus, as a consequence, if a contamination event is not the probable cause the legal limitation opens for impunity for individuals included in the database.